Simultaneous isoquercitin and gallic acid production of Aspergillus niger on Triphala byproduct under solid state fermentation in packed-bed bioreactor - Pattarabhorn Pakaweerachat; Worasaung Klinthong; Kazuhisa Ohtaguchi; Teerin Chysirichote (AIMS Agriculture and Food, 2023)
Triphala byproduct from hot-water extraction (TPB), which was a traditional process, was valorized by solid state fermentation in this research. Since the leftovers from the extraction contain high rutin and tannin contents, they were hydrolysable to isoquercitin and gallic acid, which were their monomers, respectively. Aspergillus niger, a producer of α-L-rhamnosidase and β-glucosidase, was cultured on the TPB to produce both isoquercitin and gallic acid, which were powerful antioxidants used in medical applications. The solid-state fermentation (SSF) was conducted in the three-layered packed-bed bioreactor aerated with humid air at different rates (0.1, 0.2 and 0.3 L/L/min or vvm). The highest isoquercitin and gallic acid production rates were found in the SSF, with 0.1 vvm at 1.14/h and 0.3 vvm at 3.12/h, respectively. The interaction of aeration rate and fermentation time significantly affected the fungal growth and the production of gallic acid, while the isoquercitin production was affected only by the fermentation time. Moreover, the differences of their production yields in different positions of bed along the height of bioreactor found to be useful to design the harvesting period of the fermentation products including isoquercitin or gallic acid or simultaneous isoquercitin and gallic acid. The results clearly showed that aeration, harvesting time, and position of the bioreactor were crucial in designing the process for isoquercitin, gallic acid, or both.
Keywords: Phytochemical compounds biological activities; Tannin, Tannase and Anticancer Activities; Enzyme Production and Characterization